SOSIALISASI KETAHANAN PANGAN TINGKAT RUMAH TANGGA DI DESA KALI UPA KECAMATAN TOBELO TENGAH KABUPATEN HALMAHERA UTARA - Olivia Akerina, Febrina; Patty, Zeth; Kastanja, Ariance Y.; Kour, Femsy (HIRONO : Jurnal Pengabdian Masyarakat, 2023)
Food security socialization activities carried out at the Kali Upa Village Office, Central Tobelo Sub-district, North Halmahera Regency, aim to increase community knowledge about food security, use of yards and processing and consumption of fishery products to support community food security. The methods used in this service activity are counseling, discussion and object introduction through pictures and videos to make it easier for participants to understand the material presented. The results of the activity show that there has been an increase in community knowledge regarding food security at the household level, which includes understanding the concept of food security, utilization of the surrounding environment and consumption of fishery products to support food security.